Sport, the arts, and fans’ loyalty: the role of color for sport fans - Schleifer, Ron; Tamir, Ilan (Frontiers in Psychology, 2023)
Sport fandom has attracted far-ranging research attention. Fans' commitment, loyalty, and sense of affinity are abundantly expressed in a long list of life practices. Precisely in this context, the color that identifies each sports team has also become an important element of the game but also a crucial component of fans' identities. The present article focuses on the aesthetics of team uniform colors and identifies the artistic roles they fill. Among other things, the article addresses the important role of color, for example in identifying and distinguishing figures on the pitch from the background by creating clear borders between the elements on the pitch that compete for fans' attention; in the extension of fans' emotions through the connection between team and color; in creating the opportunity for spectators to participate fully in creating the aesthetic experience on the field through the intensive use of team colors; and in enhancing a team's halo effect through the association of the team with its colors. On a deeper level, the article states that in an era of commercialized sports, the team color remains the clear and consistent symbol of the team that preserves the identity of the fans.